The Effect of pH Adjustment of 0.5% Bupivacaine on the Latency of Epidural Anesthesia. Issue 5 (September 1989) - Stevens, Rom A.; Spitzer, Loren; Chester, William L.; Brandon, David; Grueter, Jean A.; Clayton, Brian; Schubert, Armin
Abstract : pH adjustment of lidocaine and 2-chloroprocaine has been reported to decrease the latency of epidural anesthesia (EA). The effect of alkalinization of bupivacaine on onset of surgical anesthesia has not been adequately studied to date. To determine what effect raising the pH of 0.5% bupivacaine has on the latency of EA in patients undergoing lower extremity surgery, we performed a randomized, double-blind study. Forty patients were randomly divided into two groups. Group I patients received 15 ml of a local anesthetic (LA) solution containing 0.5% bupivacaine and 0.15 mEq of NaHCO3 . Group II patients received 15 ml of a standard solution of 0.5% bupivacaine. Both solutions contained freshly added epinephrine (1:200, 000). After injection of LA via Tuohy needle, sensory testing was conducted using a safety pin. The pH of the LA used for Group I was 6.96 ± 0.01 and for Group II was 5.33 ± 0.11. No statistically significant difference was found between the anesthetic parameters tested in each group. On this basis, we find no advantage of pH adjustment of 0.5% bupivacaine for EA.